UTILIZING THE FINDINGS OFINTERCULTURAL ADAPTION RESEARCH IN THE COUNSELING OF MALAYSIAN STUDENTS IN JAPAN - Ab Rahim, Ina Suryani; Hussin, Huzili; Kaur, Kuldip (Journal of Human Capital Development (JHCD), 2008)
Adaptation supports the performance and functioning of international students. Failure to adapt to the changes in the new environment would tax on well-being, exhaust the students and strain their academic performance. Counselling is one of the sources to seek assistance. Orientation and intervention programs are suitable dispensation means for information on coping mechanism and healthy adaptation. Generalization and stereotyping in dealing with adaptation problems would reduce the accomplishment of the intervention programs and the counseling (Slodzinski, 1994). Evidence also shows that the effectiveness of counseling can be affected by a client’s level or degree of acculturation into the dominant society (Cuellar, Harris & Jasso, 1980). The programs and counseling should be addressed consideration to different cultural sensitivity and needs. The significance of this paper is to point out the importance of understanding the intercultural adaptation issues in the counseling of Malaysian students in Japan by putting forward the conflicting findings from various socio-cultural adaptation studies. The main objective of this paper is to highlight the dire need for counselors to inculate the findings of specific study on international adaptation into their counseling services. The paper is aimed to extend the understanding on intercultural adaptation among Malaysian students abroad, exclusively in Japan by highlighting the conflicting findings in the to western and the Japan research scenario in terms of time factor, cultural distance factor and host language proficiency factor. Generalization and stereotyping of western cases in dealing with adaptation problems among Malaysian students in Japan to reduce the accomplishment of the intervention programs and the counseling. Keywords: counseling, intercultural adaptation, Malaysian students